Evaluación de sinergia y comportamiento de floculantes y coagulantes con dióxido de cloro, para la industria de galvanotecnia. (2022)
During the development of the document for this degree project, the capacity of chlorine dioxide as an oxidant in a heavy metal removal process is analyzed, experimented, and evaluated, based on a previous degree project in which the removal of metals for the electrochemical workshop at the CAMAN air base. Developing an initial and final characterization of the residual water, an experimentation through a jar test, an analysis of costs and relevant calculations for the development of all the work and thus achieve the correct evaluation of chlorine dioxide as an oxidant in this process.